God in Modern Alienation: Theological Reflections on Tawheed and the Trinity in a Secular Context - Elsjani Adelin Langi (Jurnal Theologia, 2025)
This study examines the phenomenon of God's alienation in modern secular societies through a comparative theological analysis of Tawheed in Islam and the Trinity in Christianity, using these concepts as its primary units of analysis. The research aims to examine how these two fundamental doctrines respond to the challenges of secularism, individualism, and materialism in shaping modern religious consciousness. Using a literature-based comparative theological approach combined with hermeneutic-analytical methods, this study integrates classical and contemporary sources, along with sociological data from global surveys, such as those conducted by the Pew Research Center and the World Values Survey. The findings reveal three key factors contributing to spiritual alienation: the crisis of transcendence, the individualization of belief, and the dominance of materialistic culture. Despite doctrinal differences, both Tawheed and the Trinity face similar struggles in maintaining theological relevance among younger and urban populations that are increasingly skeptical of religious authority. The study contributes to comparative theology by proposing a contextual model for reinterpreting the concept of divinity that balances transcendence with human experience. It also highlights the need to strengthen interfaith dialogue, digital engagement, and contextual theology to ensure that the concept of God remains a transformative moral and spiritual force in the twenty-first century.